Changes in motor cortex excitability for the trained and non-trained hand after long-term unilateral motor training. (24th April 2017) - Grothe, Matthias; Doppl, Karla; Roth, Charlotte; Roschka, Sybille; Platz, Thomas; Lotze, Martin
Highlights: We investigated intracortical facilitation (ICF) in M1 after unilateral long term hand training. Motor performance improved for both hands but ICF was only altered for the untrained hand. The ICF-decrease is associated with a transfer of training-induced improvement of performance. Abstract: Repetitive unilateral upper limb motor training does not only affect behavior but also increases excitability of the contralateral primary motor cortex (M1). The behavioral gain is partially transferred to the non-trained side. Changes in M1 intracortical facilitation (ICF) might as well be observed for both hand sides. We measured ICF of both left and right abductor pollicis brevis muscles (APB) before and after a two-week period of arm ability training (AAT) of the left hand in 13 strongly right handed healthy volunteers. Performance with AAT-tasks improved for both the left trained and right untrained hand. ICF for the untrained hand decreased over training while it remained unchanged for the left trained hand. Decrease of ICF for the right hand was moderately associated with an increase of AAT-performance for the untrained right hand. We conclude that ICF-imbalance between dominant and non-dominant hand is sensitive to long-term motor training: training of the non-dominant hand results in a decrease of ICF of the dominant hand. The ICF-decrease is associated with a transfer of training-induced improvement of performance from the non-dominant to the dominant hand.